Protection of Women's Rights in Polygamy in Indonesia - Puput Putri Utami; Asep Saepullah; Akhmad Shodikin (Journal of Law and Social Politics, 2023)
With the existence of the principle of monogamy adhered to by Law Number 1 of 1974 concerning Marriage, polygamy in Indonesia is only permitted during an emergency and if the requirements stipulated by the Law are fulfilled. However, the practice of polygamy that occurs in society is much wider and more diverse, including in the Cirebon Religious Court. One of them is case Number 910/Pdt.G/2019/PA.CN. The Petitioner was granted by the Religious Court to practice polygamy, even though the Respondent (first wife) was still able to carry out her obligations properly, had no disease or disability, and was able to give birth to offspring. According to Law Number 1 of 1974 concerning Marriage, the application must be rejected. The research method used in this study is qualitative with a descriptive-analytical approach. This research uses a type of normative legal research, namely doctrinal legal research or library research because this research is only aimed at written regulations. The results of the study show that the judge considers social justice with the consent of the first wife to be a legal consideration in granting the application for a polygamy permit as an effort to protect women's rights and in terms of civil order the Panel of Judges guarantees heirs and certainty of joint assets to save the rights of the first wife. The judge decided on a polygamy permit Number 910/Pdt.G/2019/PA.CN. granted through his suspicions and beliefs when exploring a case that was preceded by proof. By considering the benefits and harms that will arise from this polygamy and referring to the consent of the first wife, the application for a polygamy permit is appropriate to be granted even though the facultative conditions are not met in case Number 910/Pdt.G/2019/PA.CN.